PENGARUH UKURAN, NPL, CAR, LDR, DAN VARIABEL MAKROEKONOMITERHADAP PROFITABILITAS BANK BUSN NON DEVISA YANG TERDAFTAR DIINDONESIA PERIODE 2012-2015 - ANDRIAN, DWI (Jurnal Ilmu Manajemen (JIM), 2017)
The purpose of this research is to understand the influence of size, Non Performing Loan, Capital Adequacy Ratio, Loan to Deposit Ratio, and macroeconomic variable on bank profitability. For macroeconomic variable use inflation and Gross Domestic Product. To measure bank profitability in this research use Return On Asset. In this research use sample were Non Foreign Exchange National Private Commercials Bank was published financial statements period 2012-2015. The study uses a quantitative approach, and used are secondary data. The analysis technic were multiple regresion models. The result of this study indicated that size variable has no influence on bank profitability. Non Performing Loan variable has a negative significant on bank profitability. For Capital Adequacy Ratio has no influence on bank profitability. Loan to Deposit Ratio variable has a negative significant on bank profitability. Inflation variable has no influence on bank profitability. For Gross Domestic Product variable has a positive significant on bank profitability. The result indicates that Non Foreign Exchange National Private Commercial Bank should pay more attention to the NPL and LDR variable’s, beside from the external side of the bank should also consider the level of GDP. So that bank profitability can increase. Keywords: NPL, LDR, GDP, ROA<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px;" />